PERBEDAAN POSITIVE YOUTH DEVELOPMENT (PYD) BERDASARKAN JUMLAH DAN TIPE EKSTRAKURIKULER YANG DIIKUTI REMAJA DI KOTA BOGOR - Rama Adeyasa; Aida Vitayala S.Hubeis; Ninuk Purnaningsih; Dwi Sadono (Jurnal Kommunity Online, 2021)
This study has attempted to analyze the Positive Youth Development (PYD) perspectives as a measuring instrument for adolescent. 324 adolescences from 12 Senior High School both General and Vocational from Bogor were analyzed using questionnaire of quantitative study. This study has shown that there based on the number of extracurricular activities joined by student, the more they joined, the higher the score of 5Cs PYD, except for them who joined three extracurricular activities. Based on the type of extracurricular activities, C1, C2, C4, and C5 was highest for sport extracurricular activities while C3 is from the art type. Based on combination if the extracurricular activities, the highest 5Cs PYD score was found in student joined all the sport combination type, and the lowest score found in all of academic combination type